TANGGUNG JAWAB DOKTER MUDA (KO ASS) DALAM PENANGANAN KESEHATAN TERHADAP PASIEN DI RSUD ARIFIN ACHMAD PEKANBARU - Kristiningrum, Friska Dwi; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The young doctor co ass is a graduate medical student who follows secretariat co ass medical education in order to get the title of the medical profession. In undergoing the procces education of co ass young doctor co ass stationed in the hospital in order to undergo the practice of medicine action under the guidance of a master doctor or supervisor. In carrying out their education while in hospital young doctor co ass get an exception in the handling of medical to the patient, this is because the young doctor co ass has not had a SIP of that cause young doctor co ass does not have full responsibility to the patient, medical action perfomed by a young doctor co ass to be on instructions and under the authority of master doctors or supervisor. But in fact there has been a social offenses between master doctors with co ass young doctors to patients in RSUD Arifin Achmad Pekanbaru, physicians and phycisian young doctor co ass be disregarding the rights of patients to provide quality medical treatment. By law No. 29 of 2004 article 73 paragraph (2) explained that each person is prohibited to use the tools, methods or other means providing services to the people who give the impression as if the person concerned is a doctor or dentist who has has registration papers and permit practice at (SIP). Young doctor co ass under the guidance of master doctors prohibited medical action directly to the patient, where the handling of medical commited by young doctors co ass without supervison by a master doctors entitled to account for acts young doctor co ass that it is based a cooperation agreement Arifin Achmad hospital in Pekanbaru with medical faculties Riau University. Problem and goals will be discussed in this thesis is to find out how the shape og a young doctor co ass responsibilities in health care to patients at Arifin Achmad Hospitas in Pekanbaru.This kind of research is sociological because in this study the authors directly conduct research on the location or point examined in order to provide a complete and clear picture of the problems examined. This research conducted Arifin Achmad Hospital in Pekanbaru, while the sample population is a whole regard to the issues examined in this study, the data source used primary data, sekunder data and terteier data, data collection techniques used were interviews questionnaries, and literature studies.While the technique of data analysis using qualitative descriptive analysis. It can be concluded that the patients as recipients of health care perfomed by young doctor co ass entitled to hold against master doctors who is in charge that do not oversee the actionts of yong doctors co ass in providing treatment to patients in hospitals Arifin Achmad Pekanbaru. Suggestions for local governments and hospitals in order to make the policy more on the responsibilities of young doctors co ass handling of health of the patients during clerkships co ass at the hospital in order to avoid misunderstanding in providing medical actions.Keywords: responsibility-handling medical health-young doctor co ass-patient